Stuck between Mother Earth and a mother"s womb? On women, population policy and ecological sustainable development - Wyk, Tanya van (HTS teologiese studies, 2022)
This article considers how the metaphor of Mother Earth, for women, concerns a dual stance of both belonging and distance. The link between women, nature and Mother Earth is problematised by considering the possible, or contested, link between population growth and climate change, and the South African population policy specifically is considered as an example. Ecofeminism’s challenge to the perceived connection between women, motherhood and Earth, that is the ‘distance’ stance, is considered and a response to that is offered by reflecting on Mercy Oduyoye’s notion of mothering, which represents the ‘belonging’ stance. In this regard, an intercultural approach to the definition of motherhood is implied. It is ultimately indicated that for women to reclaim their own agency regarding a perceived responsibility towards nature, it is necessary to deconstruct and reconstruct ‘motherhood’ to free themselves from being stuck between Mother Earth and a mother’s womb.Contribution: This article makes a contribution to feminist studies at the intersection of gender roles and the climate crisis, as it relates to population growth and an intercultural definition of motherhood. It contributes to UN’s sustainable development agenda as it relates to both SDG 5 (gender equality) and SDG 13 (climate action).